Child learning and family mealtime environment, parenting style and family functioning among preschoolers in Hong Kong. Issue 2 (3rd April 2017) - Leung, Cynthia; Lo, Sing Kai; Tsang, Sandra; Chan, Ruth
Abstract: A two-wave longitudinal study on 470 parent–child dyads examined the impact of family mealtime environment, parenting style and family functioning on preschoolers' (three to six years old) learning. Measures included parent report on parenting style, family functioning, family meal frequency, mealtime television, feeding practice, teacher/parent report of academic competence and individual assessment of preschoolers' preschool concepts. Family mealtime environment variables were associated with pre-schoolers' learning, in addition to parenting style and family functioning, after controlling for family income and wave 1 preschoolers' learning. The results highlighted the importance of family mealtime environment on preschoolers' learning.